The Effectiveness of Quranic Counseling to Eradicate Post-Disaster Trauma Due to Psychological Nervousness and Denial of God - Ridwan, Ridwan; Wahyudi, Amien (Universitas Ahmad Dahlan, 2023)
The purpose of this study was to evaluate the effectiveness of Quranic counseling in alleviating post-traumatic stress disorder (PTSD) caused by psychological nervousness and denial of God. The research employed a single-subject quantitative design (SSQD) method, with 60 students selected through purposive sampling. Data were collected using four instruments: the PTSD Checklist, the Psychological Nervousness Scale, the Denial of Positive Experiences Scale, and a 10-point scale on 'self-full-of-regret.' Data analysis was conducted using percentage analysis techniques. The results indicated that post-disaster trauma was both directly and indirectly influenced by denial of God, leading to psychological nervousness. The study found that Quranic counseling was effective in alleviating trauma, reducing symptoms by up to 52%. These findings contribute to the development of PTSD theory by incorporating a religious perspective and offer Quranic counseling as an alternative solution